Agency over Phantom Limb Enhanced by Short-Term Mirror Therapy - Imaizumi, Shu; Asai, Tomohisa; Koyama, Shinichi (Frontiers in Human Neuroscience, 2017)
Most amputees experience phantom limb, whereby they feel that the amputated limb is still present. In some cases, these experiences include pain that can be alleviated by “mirror therapy.” Mirror therapy consists of superimposing a mirrored image of the moving intact limb onto the phantom limb. This therapy provides a closed loop between the motor command to the amputated limb and its predicted visual feedback. This loop is also involved in the sense of agency, a feeling of controlling one’s own body. However, it is unclear how mirror therapy is related to the sense of agency over a phantom limb. Using mirror therapy, we investigated phantom limb pain and the senses of agency and ownership (i.e., a feeling of having one’s own body) of the phantom limb. Nine upper-limb amputees, five of whom reported recent phantom limb pain, underwent a single 15-minute trial of mirror therapy. Before and after the trial, the participants completed a questionnaire regarding agency, ownership, and pain related to their phantom limb. They reported that the sense of agency over the phantom limb increased following the mirror therapy trial, while the ownership slightly increased but not as much as did the agency. The reported pain did not change; that is, it was comparably mild before and after the trial. These results suggest that short-term mirror therapy can, at least transiently, selectively enhance the sense of agency over a phantom limb, but may not alleviate phantom limb pain.